Methods for Developing Movement Energy in Athletes: Scientific and Practical Approach (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
The optimal role of the kinetic energy systems in the physical load of athletes. In three articles, the physiological mechanisms of the phosphagen, glycolytic and oxidative energy systems are analyzed and modern methods, training programs and nutritional strategies for their development are proposed. Based on the results of research and methods based on real sports examples.